Shooting Accuracy of Hippermaku Futsal Team in Palopo City: The Role of Physical Conditions - Akmal Akmal; Rachmat Hidayat; Ainul Fahmi; A. Heri Riswanto (JUARA : Jurnal Olahraga, 2023)
Futsal is one of the most popular sports in Palopo City. Various problems faced by Hippermaku futsal athletes in Palopo that during practice, many players are lazy for training, so only a few players participated in the exercise, and the shooting result was off target. This research aims to discover the relationship between physical conditions towards shooting accuracy. The method used is correlational descriptive quantitative. Based on the findings show that there is a significant relation between physical condition towards shooting accuracy. The conclusion of this research is to contribute positively to the Hippermaku Futsal Team of Palopo.